2021
DOI: 10.1080/23802359.2021.1899081
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the complete plastome of Aster pekinensis (Asteraceae), a perennial herb

Abstract: Aster pekinensis is a perennial herb that distributes widely in China, Korea, and Eeastern Russia. The complete plastome of A. pekinensis is reported here. It is a circular molecular of 152,815 bp in length and consists of a large single-copy region (LSC: 84,530 bp), a small single-copy region (SSC: 18,219 bp), and two inverted repeats (IR: 25,033 bp) regions. GC content is 37.3%. This plastome encodes 113 unique genes, including 79 protein-coding genes, 30 tRNAs, and 4 rRNAs. Phylogenomic analysis of 17 plast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 9 publications
(10 reference statements)
0
6
0
Order By: Relevance
“…In our study, we successfully assembled the complete plastome of A. yaoshanensis collected from Guangxi for the first time. Based on the analysis of the plastome map, we found that the structure, gene location, size and gene content of A. yaoshanensis are highly conserved, which is very similar to the plastome structure of most reported Aster plants, such as A. ageratoides ( Feng et al., 2021 ; Zhang et al., 2021 ; Wang and Liu, 2023 ). The plastomes of these Aster have a standard quadripartite structure, including two inverted repeat regions (IRs), an LSC region and an SSC region, and the general GC content was low in the whole sequence.…”
Section: Discussionmentioning
confidence: 55%
“…In our study, we successfully assembled the complete plastome of A. yaoshanensis collected from Guangxi for the first time. Based on the analysis of the plastome map, we found that the structure, gene location, size and gene content of A. yaoshanensis are highly conserved, which is very similar to the plastome structure of most reported Aster plants, such as A. ageratoides ( Feng et al., 2021 ; Zhang et al., 2021 ; Wang and Liu, 2023 ). The plastomes of these Aster have a standard quadripartite structure, including two inverted repeat regions (IRs), an LSC region and an SSC region, and the general GC content was low in the whole sequence.…”
Section: Discussionmentioning
confidence: 55%
“… 2017 ), Aster altaicus NC 072176 (this study), Aster falcifolius NC 069916, Aster lavandulifolius NC 063955, Aster pekinensis MW 255593 (Zhang et al. 2021 ), Aster polius NC 063453, Aster procerus NC 069914, Aster souliei OK 323961 (Wang et al. 2022 ), Aster sp.…”
Section: Resultsmentioning
confidence: 66%
“…belongs to the Aster genus of the Asteraceae family. Previous studies have explored the complete chloroplast genomes of various Aster species [21][22][23][24][25]. In this study, we present the first successfully assembled and annotated complete chloroplast genome of A. altaicus Willd., collected from the Tibetan Plateau.…”
Section: Discussionmentioning
confidence: 99%